Sistem Informasi Manajemen Perawatan Mesin Perkakas Untuk Menginventory dan Pengelompokan Permesinan pada Politeknik Negeri Fakfak - Rusdin (Jurnal Informasi, Sains dan Teknologi, 2025)
Inventory is one of the supports for an industry in carrying out its activities, both in the grouping of a machine and the management system in machinery to improve a job. One of the efforts to improve service that can be undertaken is by increasing the amount of inventory owned. The increasing amount of inventory also requires proper inventory management using a database system. Microsoft Access to assist in database design. Before being stored in the database, data and information regarding the inventory will be grouped using the concept of Group Technology (GT) to facilitate the data storage process. Users can be obtained by gathering information from recording staff and the laboratory head through interviews. In addition to defining user needs, the design of the Entity Relationship Diagram (ERD) and Data Flow Diagram (DFD) was carried out to understand the existing system. To analyze the existing system, an analysis is conducted based on Performance, Information, Economy, Control, Efficiency, and Service (PIECES). The results of the validation test, verification test, and prototype test show that the weaknesses of the existing system can be improved and user needs can be met. To identify the weaknesses of the system, a PIECES analysis can be conducted on both the old and new systems. Meanwhile, to determine whether user needs have been met, adjustments can be made by aligning user needs with the prototype through validation and verification tests.